2011
DOI: 10.1038/modpathol.2010.201
|View full text |Cite
|
Sign up to set email alerts
|

A novel t(4;22)(q31;q12) produces an EWSR1–SMARCA5 fusion in extraskeletal Ewing sarcoma/primitive neuroectodermal tumor

Abstract: Over 90% of Ewing sarcoma/primitive neuroectodermal tumors (PNETs) feature an 11;22 translocation leading to an EWSR1-FLI1 fusion. Less commonly, a member of the ETS-transcription factor family other than FLI1 is fused with EWSR1. In this study, cytogenetic analysis of an extraskeletal Ewing sarcoma/PNET revealed a novel chromosomal translocation t(4;22)(q31;q12) as the sole anomaly. Following confirmation of an EWSR1 rearrangement by the use of EWSR1 breakpoint flanking probes, a fluorescence in situ hybridiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(53 citation statements)
references
References 48 publications
(50 reference statements)
0
52
0
1
Order By: Relevance
“…Later studies showed that SNF2H is essential for proliferation of adult hematopoietic progenitors, in line with the first observations (43). More recently, SNF2H was identified as a fusion partner of EWSR1 in Ewing sarcoma/primitive neuroectodermal tumors, and the tumorigenic potential of the chimeric protein was documented (46). Furthermore, higher levels of SNF2H have been reported in gastric cancer than in normal mucosa, suggesting a role in malignancy (17).…”
mentioning
confidence: 49%
“…Later studies showed that SNF2H is essential for proliferation of adult hematopoietic progenitors, in line with the first observations (43). More recently, SNF2H was identified as a fusion partner of EWSR1 in Ewing sarcoma/primitive neuroectodermal tumors, and the tumorigenic potential of the chimeric protein was documented (46). Furthermore, higher levels of SNF2H have been reported in gastric cancer than in normal mucosa, suggesting a role in malignancy (17).…”
mentioning
confidence: 49%
“…The especially 4q31 locus was significantly overrepresented in our patients (Table 1) (Figure 2). Cytogenetic analysis of an extraskeletal Ewing sarcoma/ primitive neuroectodermal tumors (PNETs) revealed a novel chromosomal translocation t(4;22)(q31;q12) as the sole anomaly (Sumegi et al, 2011). Recent gene studies of chronic obstructive pulmonary disease (COPD) implicate genetic variants on the chromosomal 4q31 locus.…”
Section: Discussionmentioning
confidence: 99%
“…[47] EWSR1-PATZ t(1;22)(p36.1;q12)[with inv (22)] Mastrangelo et al . [48] EWSR1-SP3 t(2;22)(q31;q12)…”
Section: Mutationsunclassified